Kepemimpinan Kepala Desa dalam Mewujudkan Good Governance pada Perspektif New Public Leadership di Desa Krikilan Kecamatan Driyorejo Kabupaten Gresik - Much Sari’ul Fahmi; Anggraeny Puspaningtyas; M Kendry Widiyanto (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The aim of this research is to analyze and describe how the Village Head's leadership is in realizing Good Governance from a New Public Leadership perspective in Krikilan Village, Driyorejo District, Gresik Regency. This research data collection technique was carried out through observation and interviews in the field. The results of this research are that the Village Head's leadership in realizing Good Governance from the perspective of New Public Leadership in Krikilan Village, Driyorejo District, Gresik Regency has shown that indicators of the Leadership Role in terms of Accountability, Transparency and Openness have not been fully implemented well. Meanwhile, Network Management indicators in terms of Accountability, Transparency and Rule of Law have been implemented well. Meanwhile, indicators of Public Value as a Result of Effective Public Leadership in terms of Accountability, Transparency and Rule of Law have been implemented well. Furthermore, the Accountability indicators in terms of Network Management and Public Value as a Result of Effective Public Leadership have been implemented very well, while the Transparency indicators in terms of Network Management and Public Value as a Result of Effective Public Leadership have been implemented well. Then the Openness indicators in terms of Leadership Role, Network Management, and Public Value as a Result of Effective Public Leadership have not been fully implemented properly and optimally. Finally, the indicators for the Rule of Law in terms of Leadership Role, Network Management, and Public Value as a Result of Effective Public Leadership have been implemented very well.